2019
DOI: 10.1073/pnas.1902532116
|View full text |Cite
|
Sign up to set email alerts
|

Arabinogalactan protein–rare earth element complexes activate plant endocytosis

Abstract: Endocytosis is essential to all eukaryotes, but how cargoes are selected for internalization remains poorly characterized. Extracellular cargoes are thought to be selected by transmembrane receptors that bind intracellular adaptors proteins to initiate endocytosis. Here, we report a mechanism for clathrin-mediated endocytosis (CME) of extracellular lanthanum [La(III)] cargoes, which requires extracellular arabinogalactan proteins (AGPs) that are anchored on the outer face of the plasma membrane. AGPs were colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…The dynamics of SYT1–GFP and SYT5–GFP relocalization are consistent with EPCS remodeling being triggered by the slow internalization of REEs to the cytosol (L. Wang et al, 2014 , 2016 , 2019 ). In this scenario, the addition of EGTA, a polydentate chelator that forms stable complexes with both Ca 2+ and REEs ( Tei et al , 2010 ), should maintain REEs in the extracellular space and prevent the REE-induced SYT1–GFP and SYT5–GFP relocalization.…”
Section: Resultssupporting
confidence: 68%
“…The dynamics of SYT1–GFP and SYT5–GFP relocalization are consistent with EPCS remodeling being triggered by the slow internalization of REEs to the cytosol (L. Wang et al, 2014 , 2016 , 2019 ). In this scenario, the addition of EGTA, a polydentate chelator that forms stable complexes with both Ca 2+ and REEs ( Tei et al , 2010 ), should maintain REEs in the extracellular space and prevent the REE-induced SYT1–GFP and SYT5–GFP relocalization.…”
Section: Resultssupporting
confidence: 68%
“…[ 63 ] Some possible mechanisms include: 1) rare earth ions (RE 3+ ) induced hormesis, [ 64 ] 2) directly or indirectly affect photosynthesis, [ 56 ] 3) RE 3+ interfere with the biological effects of Ca 2+ by inhibiting or replacing Ca 2+ at the cellular level, [ 52 ] 4) activate endocytosis in plant cells. [ 65 ] Increases of the contents of soluble protein, soluble sugar, starch, and vitamin C found in this study can be attributed to the above mentioned stimulant effect of Ce 3+ ions on photosynthesis. However, Ce 3+ ion treatments decreased the contents of reducing sugars and phenolic compounds which have strong antioxidant properties.…”
Section: Discussionmentioning
confidence: 57%
“…In mammals, E-Syt1 aggregates and concentrates at membrane junctions following a rise in [Ca 2+ ] cyt [28] . However, in Arabidopsis, a similar behavior is observed when PM Ca 2+ channel blockers [39-42] /endocytosis inductors [43, 44] are used. This differential behavior is difficult to reconcile unless endocytosed REEs were able to trigger intracellular Ca 2+ signals, effectively offsetting their effect as PM Ca 2+ channel blockers.…”
Section: Discussionmentioning
confidence: 66%
“…Previous reports have shown that long-term treatments with REEs induce endocytosis and promote the release of REEs to the cytosol [43, 44] , so we asked whether REE-endocytosis underlies the observed changes in SYT1-GFP and SYT5-GFP localization following such a treatment. Figures 5A-5C show that the REE treatments promote the accumulation and internalization of phosphatidylinositol-4-phosphate (PI4P) containing-vesicles, as indicated by the ratiometric sensor citrine 1xPH FAPP1 [45] .…”
Section: Resultsmentioning
confidence: 99%